Ancient Art in Seals (1980)
Essays by Pierre Amiet (The Mythological Repertory in Cylinder Seals of the Agade Period (c. 2335-2155 B.C.)), Nimet Özgüç (Seal Impressions from the Palaces at Acemhöyük), and John Boardman (Greek Gem Engravers, Their Subjects and Style); Edited and Translated by Edith Porada; lectures given at Pierpont Morgan Library, Dec. 1976; translations from French and Turkish by E. Porada and Machteld J. Mellink.